Implementasi Pembelajaran Al-Qur'an Di Pesantren Putri Ummahatul Mukminin Timika Papua Bagi Anak Asli Papua - Azhar M, Andi Ikhsan; Choeroni, Choeroni; Muchtar, Asmaji (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the challenges, opportunities, and impacts of implementing Qur'an learning at the Putri Ummahatul Mukminin Islamic Boarding School in Timika, Papua, for native Papuan children. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that the main obstacles include difficulties in understanding Arabic due to the students’ diverse local language backgrounds, a shortage of qualified Qur'an teachers, and inadequate learning facilities. On the other hand, there are significant opportunities in utilizing mobile-based Qur'an applications and applying contextual learning approaches that incorporate Papua’s local culture into the teaching process. Qur'an learning has positively contributed to students' character development, particularly in fostering discipline, responsibility, and empathy. This research recommends intensive training for teachers, the enhancement of learning facilities, and broader use of culturally relevant educational technology.